Legitimacy Strategies: SDG Disclosure, Earnings Management, and Accounting Changes in Indonesian Banking - Santoso, Eko Budi; Yusup, Adi Kurniawan; Triani, Ni Nyoman Alit (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2026)
This study investigates the relationship between Sustainable Development Goals (SDGs) disclosure and earnings management in the Indonesian banking. The research addresses whether SDG disclosure reflects a symbolic or substantive legitimacy strategy by examining its association with opportunistic accounting behavior. The sample comprises the listed Indonesian banks for the 2016 to 2023 period, yielding 157 firm-year observations. Regression analysis with robust standard errors is employed to test the hypotheses and explore the moderating role of PSAK 71 in the relationship. The findings reveal that SDGs disclosure is positively associated with earnings management. Moreover, this relationship becomes stronger after PSAK 71 implementation, which implies enhanced managerial discretion, suggesting a symbolic function. These results are consistent for overall SDG disclosure, across SDG pillars, and across model specifications. These findings suggest that sustainability disclosure may be used as a channel for opportunistic behavior, particularly in contexts where accounting changes expand the scope of managerial discretion.